The mechanisms by which external school evaluation in Iceland influences internal evaluation and school professionals' practices - Björk Ólafsdóttir; Jón Torfi Jónasson; Anna Kristin Sigurðardóttir; Thor Aspelund (Taylor & Francis Group, 2022)
The main purpose of this research is to analyse school principals' and teachers' attitudes towards external school evaluation in Iceland, in particular, the ways in which they consider the evaluation affects their schools' internal evaluation and drives changes in their own practices. The study uses a quantitative method and is based on a survey conducted among principals and teachers in 22 schools that were externally evaluated during the years 2013 to 2015. The results indicate a positive attitude towards external school evaluation among both teachers and principals. Acceptance, setting expectations, and teacher participation were found to be significant predictors of perceived changes in internal evaluation in the teachers' data. However, only acceptance significantly explained perceived changes in teaching practices. In the principals' data, the only variable that had a significant association with perceived changes in internal evaluation was setting expectations, and only acceptance had a significant association with perceived changes in leadership practices. In accordance with the hypothesis of this study, the results underpin the importance of acceptance of the evaluation feedback and setting expectations through quality standards. However, contrary to the hypothesis, external stakeholder involvement did not prove to be a strong determinant of change as perceived by principals.